Metodos de multiplicacion acelerada de material genetico promisorio de yuca Manihot esculenta Crantz - Toro, Julio C.; Roca, W.; Cock, James H. (International Center for Tropical Agriculture, 1983)
Two methods of rapid propagation of promissory cassava genetic material are described in detail: by shoots on 2-node stem sections and by single leaf-bud cuttings. (CIAT)